Increased zinc finger protein zFOC1 transcripts in gastric cancer compared with normal gastric tissue. Issue 3 (1st June 2003) - Stephen, R L; Crabtree, J E; Yoshimura, T; Clayton, C L; Dixon, M F; Robinson, P A
Abstract : Background: Screening of cDNA arrays of the IMAGE library identified human zFOC1 as a differentially expressed cDNA that was upregulated in KATO III gastric cancer cells following stimulation with the gastric pathogen Helicobacter pylori. Aims: To determine the expression of zFOC1 in gastric mucosa with and without H pylori infection and in patients with gastric cancer. Results: zFOC1 is localised on chromosome 12q24.3 and encodes a zinc finger protein. Expression studies in human H pylori infected and uninfected gastric biopsies, gastric tumours, and gastric cancer cell lines revealed that zFOCI gene transcripts are significantly higher in gastric cancer than in non-cancerous gastric tissues. Conclusions: The zFOC1 gene appears to be a tumour marker associated with gastric cancer.